Body Mass Index, Waist-Hip Ratio and Fasting Blood Glucose Levels amongst the University Students - Oktariza, Rury Tiara; Kalanjati, Viskasari Pintoko; Tirthaningsih, Ni Wajan (Folia Medica Indonesiana, 2021)
Overweight and obesity have been correlated to the higher risk for developing metabolic diseases in later life, i.e. DM type 2. We study the body mass index (BMI), the waist to hip ratio (WHR) and the fasting blood glucose levels (FBG) in the seemingly healthy male and female university students to comprehend these variables amongst the youth in Indonesia in 2019. The BMI and WHR of 150 male and female students aged 18-22 years old of the IIKBW, Kediri were measured by standardised anthropometry. The FBG was measured after 8 hours-minimum of fasting from the capillary blood drop using glucometer. Data was then analysed using SPSS 17 with level of significance of p<0.05. According to Asia-Pacific BMI classification, students were 30.7% obese with males significantly higher than females (p=0.016), 18% overweight (significantly higher in females, p=0.04), 36% normal and 15.3% underweight.When compared between genders, the WHR is significantly higher in males (p<0.001); whilst no significant differences in FBG (p=0.6). Four males and 5 females with FBG â‰¥ 100 mg/dl, whereas others were within normal limits. There are positive significant correlations between BMI and WHR in males and females (r=0.777, p<0.001; r=0.54, p<0.001, respectively). There is a significant positive correlation between the BMI and FBG with r=0.217, p=0.008; and between the WHR and FBG with r=0.21, p=0.01 amongst all students. In this study, male students have significantly higher BMI and WHR than females. Higher FBG was well observed in students with either higher BMI or WHR.